SEAWATER AS A REAGENT IN THE FLUE GAS DESULPHURISATION PROCESS - Martin Bricl (Journal of Energy Technology, 2025)
Sulphur dioxide is a poisonous substance that is vastly formed in the process of fossil fuel burning inside the steam boiler of a thermal power plant, or any other industrial plant that uses fossil fuels as a prime source of energy. The technology involved in cleaning the sulphurous component from the raw, uncleaned flue gas flow in fossil fuel-based power and industrial plants is a form of technology that has been present for the last three decades and is constantly evolving in its characteristics and performance to deliver the highly-efficient flue gas cleaning procedure. The standard and technological mature technical solutions for flue gas desulphurisation of untreated flue gases are comprised of dry, semi-dry, and wet flue gas desulphurisation processes. The most frequently used solution, as well as that most applicable to most existing and new fossil fuelbased thermal power plants, is the wet flue gas desulphurisation process. The aforementioned wet cleaning process may be limestone-based (LFOS – Limestone Forced Oxidation System) or magnesium-based (MEL – Magnesium Enhanced Limestone). The paper focuses on the remaining wet flue gas desulphurisation procedure, one which is neither widely-present nor known within the industry – the SWFGD (Seawater Flue Gas Desulphurisation) process. This process has numerous advantages, including the presence of a costless reagent in vast amounts (seawater), the optimisation of the plant’s design, and those linked to operational costs. We will present the flue gas cleaning process and its chemical aspects through a description of the process. We will then explore the main advantages and disadvantages of the corresponding process, as well as undertaking and presenting a comparative analysis between the main three wet flue gas desulphurisation processes (LFOS, MEL & SWFGD), taking into consideration all crucial points of each aforementioned wet flue gas cleaning process. As stated before, the main intention of wet desulphurisation processes is to remove the acid components from the untreated flue gas flow. In the process of doing this, the formation of by-products and effluent occurs, both of which have different impacts on the environment. Within the scope of this article, we will evaluate the environmental impact of the resulting by-products of each of the corresponding wet flue gas desulphurisation processes.